Representation of Parental Parenting Patterns in the Development of Low Resilience Character - Rahman, Fadhila Dwi; Asep Kurnia Jayadinata; Dhea Ardiyanti (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2025)
Parenting patterns play a crucial role in shaping children’s character development, particularly among those with low levels of resilience. Positive communication between parents and children further contributes to healthy developmental outcomes by fostering supportive and responsive interactions within the child’s immediate environment. This study aims to explore the representation of parenting patterns and their implications for the character development of children with low resilience. A qualitative research method with a case study approach was employed in Purwakarta District, West Java. Data were collected through in-depth interviews with three parents and one teacher, direct observation of children aged 4–6 years, and supporting documentation. The findings indicate that the application of authoritarian and permissive parenting styles is associated with lower levels of resilience in children, largely due to limited opportunities for developing coping skills and adaptability when facing challenges. In contrast, positive and constructive parent–child communication was found to support more favorable character and developmental outcomes. This study offers important insights for parents by highlighting effective strategies for fostering greater independence and responsibility in children, while also acknowledging the influence of the surrounding social and cultural environment. Overall, the study underscores the significance of appropriate parenting patterns in supporting the development of both character and resilience in early childhood, in alignment with Sustainable Development Goal (SDG) 4 on quality education.